Development of sustainable development goals disclosure index for higher education institutions/ Yussri Sawani, Corina Joseph& Siow Hoo Leong - Sawani, Yussri; Joseph, Corina; Siow, Hoo Leong (2023)
The objective of this paper is to develop a sustainable development goals disclosure index for higher education institutions (HSDI). The paper covers an inclusive evaluation of international and national guidelines and literature relating to disclosures about sustainable development goals information. Content analysis is employed to extract and classify the SDG related indicators from these sources. A scoring method is proposed to measure the HSDI based on the indicators. The final four categories of each SDG, with a total of 187 indicators that are up for assessment, have been developed into an instrument. The proposed HSDI is to measure the commitment undertaken by Malaysian higher education institutions in realising the SDG agenda. It is the first version of such index designed for use by institutions of higher education. This paper addresses the concerns that are relevant to the best practices that higher education institutions might implement to achieve the SDGs.